INTENSIVE TREATMENT IS SUITABLE FOR PATIENTS WITH LOW LEVEL OF BLOOD PRESSURE VARIABILITY: A SECONDARY ANALYSIS OF SPRINT. (April 2021) - Tsoi, Kelvin; Yiu, Karen; Sit, Ken; Lee, Eric; Wong, Samuel
Abstract : Objective: Visit-to-visit blood pressure variability (BPV) is a predictor of cardiovascular diseases (CVD). The Systolic Blood Pressure Intervention Trial (SPRINT) showed that intensive hypertensive treatment (targeted at a systolic BP of less than 120 mmHg) can further reduce the risk of CVD and related mortality without additional risk of serious adverse events (SAE). However, the benefit of intensive treatment for patients with different BPV remained controversial. Design and method: This study re-analyzed the data from SPRINT through the NHLBI data repository from National Institute of Health. Primary outcomes were cardiovascular related events and mortality. Life-threatening events and hospitalization were reported as the SAE. BPV is defined by the mean absolute residuals of individual linear regression of 18-month BP readings. The k-means clustering, a machine learning algorithm, was applied to stratify subjects into low, medium and high levels of BPV. Patients with primary outcomes in the first 18 months were excluded in this study. Univariate and multivariate analyses were performed to investigate the association between BPV groups and benefits of intensive treatment. Patient's characteristics including age, gender, history of CVD, were treated as confounding factors. Hazard ratios (HR) with 95% confidence intervals (CI) were reported. Results: A total of 7, 863 subjects were included, in which 1, 018 (12.9%), 3, 181 (40.5%) and 3, 664 (46.6%) were classified into low, medium and high levels of BPV, respectively (Figure 1). In the multivariate analyses, intensive treatment showed to have a significant reduction on primary outcomes for those with low level of BPV (HR 0.59; 95% CI, 0.40–0.89), but not for those with medium and high levels of BPV (Table 1). SPRINT reported that intensive treatment did not increase risk of SAE, but this study found an increased risk of SAE among patients with high level of BPV (HR 1.24; 95% CI, 1.02–1.52). Figure. No caption available. Conclusions: Intensive treatment only shows the cardiovascular benefit on the patients with low level of BPV, but it increases risk of SAE for those with high level of BPV. Personalized recommendation on the use of intensive treatment should be recommended.